The role of organisational infrastructure in successful ERP implementation: an empirical study by hierarchical regression and PCA. (1st January 2012) - Azadeh, Ali; Afshari-Mofrad, Masoud; Khalojini, Masoud
Organisations face considerable challenges in implementing and using ERP systems. Several researchers have tried to study different aspects of this system. In this paper, based on literature review and experts' interviews, a conceptual model is proposed which poses that technical and organisational infrastructures have an intervening role in the relationship between critical success factors and ERP performance. A 40-item questionnaire is used for data collection and analysis. Hierarchical regression results proved that at 95% confidence level, infrastructure variable plays a moderating role in the relationship between critical success factors and ERP performance. Also, principal component analysis (PCA) and latent moderated structural equations (LMSs) technique are used to validate the results of hierarchical regression. Results show that organisational infrastructure has the most important effect on ERP performance and 'strategic goals' is the most important critical success factor. To our knowledge, this is the first study which is concerned with the moderating role of organisational infrastructures in the relationship between ERP critical success factors and performance.